Third and Fifth Order IMDs at Carrier Position - Mohamad Kadim, Suaidi; Yong, Lisa; Awangku Abdul Rahman, Pgn. Hj. Yusof (IEEE, 2007)
The third, instead of the fifth order intermodulation distortion (IMD3), is often thought to limit the radio-over-fibre system performance as it tends to fall in-band. The Golomb Ruler based frequency plan can overcome this IMD3 problem. However, its effect on the IMD5 is not known. A laser model was derived based on Volterra Series with electrical parasitics to simulate the carrier position IMD3 and IMD5 for the Golomb Ruler and equally spaced frequency plans at low and high RF input level, supported by low bias current. The IMD5 was more dominant than the IMD3 for the equally spaced frequency plan at high RF input level. The opposite was observed at low RF input. The Golomb Ruler based frequency plan led to no IMD3s but low levels of IMD5 were still present the carrier position but they were lower than those due to the equal frequency spaced channels.